The Maintenance and Violation of the Politeness Principle in Ice Blue by Emma Jameson - Ulfa, Chery Narasyah Chiora; Pradipta, Bramantya (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This study aims to analyse how politeness maxims are either maintained or violated in the utterances of Hetheridge and Kate in the novel Ice Blue. The study applies Leech’s (2014) Seven Maxims of Politeness Principle and employs a descriptive qualitative method. The findings reveal that Hetheridge maintains approximately 54 politeness maxims and violates around 55 politeness maxims, while Kate maintains about 73 politeness maxims and violates around 52 politeness maxims. Both main characters apply all seven maxims; however, Hetheridge does not employ the sub-maxim Opinion (Reticence), and Kate does not employ both the Opinion (Reticence) and Obligation (Hearer to Speaker) maxims. Beyond identifying the types and frequencies of maxims maintained and violated by the main characters, this study also found that not all violations reflect rudeness or impoliteness. In many cases, violations occur to fulfil professional duties or to foster interpersonal relationships, showing that politeness strategies are often adapted based on context and communicative goals.